Pengalaman Penyembuhan Luka Ulkus Diabetik pada Penderita Diabetes Mellitus - Madani, Isnynda; Ismafiaty, Ismafiaty; Yuswandi, Yuswandi (Yayasan Healing and Healthcare Education, 2024)
This research was motivated by the observations of researchers who saw that diabetes mellitus is one of the diseases with the highest cause of death in the world and there are still many DM patients who still lack DM care management which causes complications that often occur in DM, namely diabetic ulcers. The issue of diabetic ulcers is still often under-appreciated and poorly understood either due to lack of knowledge or other reasons. In this case, Diabetic Ulcers can still be healed according to good and correct wound care. This study has the aim of exploring the experience of healing Diabetic Ulcers in people with Diabetes Mellitus. The research design used is qualitative descriptive research with a phenomenological approach. The data collection method used is purposive sampling. Participants in this study amounted to 5 participants. Data was collected through in-depth interviews. Data analysis used the stages of the process according to the colaizzi. The results of the study produced five main themes, namely: the process of occurrence of diabetic ulcers in patients, changes experienced by patients with diabetic ulcers, obstacles experienced by diabetic ulcer patients, management of patients with diabetic ulcers, and efforts to achieve healing in diabetic ulcer patients.